2006
DOI: 10.1109/lpt.2006.875324
|View full text |Cite
|
Sign up to set email alerts
|

Cascadability assessment of a 2R regenerator based on a saturable absorber and a semiconductor optical amplifier in a path switchable recirculating loop

Abstract: We assess a new 2R regenerator based on a microcavity saturable absorber and a semiconductor optical amplifier. Cascadability is demonstrated and the impact of regeneration span is studied in a 10-Gb/s two-path recirculating loop. A wavelength study demonstrates the tunability of the device over 13 nm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Then, we estimate first VHTE in the wavelengths range from 1.13 to 1.77 µm, according to Kataura plot [15,17], as narrowest expected wavelength window of resonant SWNT. This part of SWNT diameter distribution lead to an expected useful distribution of FOTE, matching telecom window near 1.55 µm, where excitonic optical transition of QW has already been exploited [8,9].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Then, we estimate first VHTE in the wavelengths range from 1.13 to 1.77 µm, according to Kataura plot [15,17], as narrowest expected wavelength window of resonant SWNT. This part of SWNT diameter distribution lead to an expected useful distribution of FOTE, matching telecom window near 1.55 µm, where excitonic optical transition of QW has already been exploited [8,9].…”
Section: Introductionmentioning
confidence: 94%
“…After propagation in long-haul-fibre and reamplification, damaged high-bit-rate optical telecom signal can also be cleaned at zero level, thanks to the SA OFF state, leading to better error-bit-ratio and higher transmission quality of telecommunications. Excitonic optical properties of nanomaterials-based SA, such as quantum wells (QW) nanostructures (2D-nanomaterials), have already demonstrated huge potential for such signal regeneration [8], in comparison to bulk materials. However, fabrication of these ultrafast 2D-nanostructures-based SA need complex and expensive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Different solutions were investigated so far with a SA. At 10 Gbit/s, the dynamic response of a semiconductor optical amplifier (SOA) was used to limit the intensity fluctuations [3]. At 40 Gbit/s, two solutions were investigated.…”
Section: B Dynamic Of the Power Limitermentioning
confidence: 99%
“…Semiconductor-based saturable absorbers (SA) are particularly attractive because of their small size, passive behavior and large bandwidth. They have demonstrated their strong potential for high bit-rate optical regeneration at 10 Gbit/s, 40 Gbit/s and 170 Gbit/s [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the role of the recovery time of the device which plays a decisive role in the timing jitter accumulation [23], it was shown that the transformation of pulses with amplitude noise through a reshaping gate leads to pulse width variations leading to a pseudo-timing jitter [18] limiting the transmission. The impact of the span between 2R regenerators [24] and the slope of the transmission function of the NLOG [25] were studied. These studies have shown that the optimum transmission was obtained for the best compromise between amplitude noise and timing jitter accumulation.…”
Section: Review Of Optical Long Haul Transmission Experiments Using Omentioning
confidence: 99%